Peace through Consumer Education: A Discussion Paper - McGregor , Sue LT (Nurture, 2011)
After distinguishing a culture of peace from a consumer culture, elucidating the challenges of finding peace in a consumer society and comparing consumer education to peace education, the paper proposes potential synergy to be gained from merging aligned concepts from peace education and consumer education so we can view consumer education in and of itself as a vehicle for peace. It presents, for the first time, a novel approach to consumer education, framing it as a way to strive for peace. Education about consuming (fact-based) and education for consuming (value- and ideologically-based) are juxtaposed against peace through consumer education, drawing insights from well-established approaches in peace education and sustainability education. Peace through the consumer education process would lead people from being focused on their own self-interest to being concerned for the welfare of others, other species and the planet - peace through consumption.